An interlaboratory comparison to quantify oxidative potential measurement in aerosol particles: challenges and recommendations for harmonisation - Dominutti, Pamela A.; Jaffrezo, Jean-Luc; Marsal, Anouk; Mhadhbi, Takoua; Elazzouzi, Rhabira; Rak, Camille; Cavalli, Fabrizia; Putaud, Jean-Philippe; Bougiatioti, Aikaterini; Mihalopoulos, Nikolaos; Paraskevopoulou, Despina; Mudway, Ian; et al. (Atmospheric measurement techniques, 2025)
This paper presents the findings from a collaborative interlaboratory comparison exercise designed to assess oxidative potential (OP) measurements conducted by 20 laboratories worldwide. This study represents an innovative effort as the first exercise specifically aimed at harmonising this type of OP assay, setting a new benchmark in the field. Over the last decade, there has been a noticeable increase in OP studies, with numerous research groups investigating the effects of exposure to air pollution particles through the evaluation of OP levels. However, the absence of standardised methods for OP measurements has resulted in variability in results across different groups, rendering meaningful comparisons challenging. To address this issue, this study engages in an international effort to compare OP measurements using a simplified method (with a dithiothreitol (DTT) assay). Here, we quantify the OP in liquid samples to focus on the protocol measurement itself, while future international OP interlaboratory comparisons (ILCs) should aim to assess the whole chain process, including the sample extraction. We analyse the similarities and discrepancies observed in the results, identifying the critical parameters (such as the instrument used, the use of a simplified protocol, the delivery and analysis time) that could influence OP measurements and provide recommendations for future studies and interlaboratory comparisons even if other crucial aspects, such as sampling PM methods, sample storage, extraction methods and conditions, and the evaluation of other OP assays, still need to be standardised. This collaborative approach enhances the robustness of the OP DTT assay and paves the way for future studies to build on a unified framework. This pioneering work concludes that interlaboratory comparisons provide essential insights into the OP metric and are crucial to move toward the harmonisation of OP measurements.